Volatility cones and volatility arbitrage strategies – empirical study based on SSE ETF option. Issue 2 (15th May 2017) - Pan, Hong Yu Xin; Song, Jun
Abstract : Purpose: Using volatility cones as the estimate of actual volatility instead of GARCH models, the purpose of this paper is to explore whether volatility arbitrage strategy can provide positive profits and how the transaction costs existed in the real market affect the effectiveness of volatility arbitrage strategy. Design/methodology/approach: A number of hedging approaches proposed to improve the hedging results and final returns of Black-Scholes model are analyzed and compared. Findings: The general finding is that volatility arbitrage strategy can provide satisfactory returns based on the samples in Chinese market. Regarding transaction costs, the variable bandwidth delta and delta tolerance approach showed better results. Besides, choosing futures together with ETFs as hedging underlying can increase the VaR for better risk management. Practical implications: This paper offers a new method for volatility arbitrage in Chinese financial market. Originality/value: This paper researches the profitability of the volatility arbitrage strategy on ETF 50 options using volatility cones method for the first time. This method has advantage over the point-wise estimation such as GARCH model and stochastic volatility model.